TOXOPLASMOSIS A GLOBAL THREAT TO ALL VERTEBRATES: TRENDS IN DIAGNOSTIC METHODS - A. A. Bajwa; S. Islam; I. Rashid; K. Ashraf; H. Akbar; W. Shehzad (Journal of Animal and Plant Sciences, 2014)
Toxoplasma gondii is globally widespread obligate intracellular parasitic protozoan,It affects almost all warm-blooded animals including man. More than one third of human population is infected by this parasite. It can cause life threatening diseases both in immunocompromised as well as immunocompetent hosts. The symptoms of the disease arefever, seizures and ataxia. The parasite has heteroxenous lifecycle and reproduce both sexually and asexually. Sexual cycle is limited to the members of felidae while the asexual cycle completes in mammals and birds. The transmission of parasite to human occurs either by ingestion of poorly cooked meat of infected animals or by accidental intake of food contaminated with cat feces. The infection by toxoplasma results in acute disease, latent infection may also occur. In order to diagnose the disease different diagnostic methods are used like fecal microscopy, a primitive technique is still in use. Different molecular based approaches like serological methods for parasite diagnosis including Enzyme Linked Immunosorbent Assay, Indirect Fluorescence Antibody Test, Modified Agglutination Test and many others are used for pathogen diagnosis by targeting stage specific immunoglobulins. DNA based approaches like PCR have made a significant advancement in the diagnoses of many pathogens includingT. gondii. Nested-PCR is considered to be more sensitive in diagnosis of toxoplasmosis. For more accurate and sensitive parasite detection, Real-Time PCR is more useful. This review is an attempt to highlight the global threat of the parasite. In addition; different diagnostic approaches are reviewed ranging from classical methods to recent advancements in molecular techniques.
Keywords: ELISA; Parasite; PCR; Toxoplasmagondii